2020
DOI: 10.1111/ejn.14857
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between LGMN and Alzheimer’s disease in the Southern Han Chinese population

Abstract: Recently, functional studies have demonstrated that legumain (LGMN) cleaves both amyloid β-protein precursor and tau, promoting senile plaques and formation of neurofibrillary tangles, which may play a crucial role in the pathogenesis of Alzheimer's disease (AD). However, the genetic role of LGMN in AD has not been clearly elucidated. Here, we used Sanger sequencing to investigate the single independent (single-variant association test) and cumulative (gene-based association test) effects of variants in the LG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In contrast, a decreased serum concentration of LGMN was detected with the opposite result compared to the above proteins, i.e., deletion of LGMN is associated with the alleviation of synapse loss ( Zhang et al, 2014 ). However, a recent human trial did not confirm previous reports, according to which LGMN was a driver of the process of AD development ( Zhang et al, 2020 ). Interestingly, the present proteome analysis revealed that (neuro-) inflammatory pathways were affected by HHCys in both directions: aside from the elevation of pro-inflammatory IL1a serum level ( Dinarello, 2018 ), concentrations of other protein markers were decreased in comparison to KI control mice (IL23R, CCL2, CXCL9, S100A4, WISP1, and EDA2R), indicating also anti-inflammatory effects ( Teng et al, 2015 ; Verhelst et al, 2015 ; Martin and Delarasse, 2018 ; Ambartsumian et al, 2019 ; Chen and Li, 2020 ).…”
Section: Discussionmentioning
confidence: 65%
“…In contrast, a decreased serum concentration of LGMN was detected with the opposite result compared to the above proteins, i.e., deletion of LGMN is associated with the alleviation of synapse loss ( Zhang et al, 2014 ). However, a recent human trial did not confirm previous reports, according to which LGMN was a driver of the process of AD development ( Zhang et al, 2020 ). Interestingly, the present proteome analysis revealed that (neuro-) inflammatory pathways were affected by HHCys in both directions: aside from the elevation of pro-inflammatory IL1a serum level ( Dinarello, 2018 ), concentrations of other protein markers were decreased in comparison to KI control mice (IL23R, CCL2, CXCL9, S100A4, WISP1, and EDA2R), indicating also anti-inflammatory effects ( Teng et al, 2015 ; Verhelst et al, 2015 ; Martin and Delarasse, 2018 ; Ambartsumian et al, 2019 ; Chen and Li, 2020 ).…”
Section: Discussionmentioning
confidence: 65%
“…TTR and GSN, down regulated in PD, are known for their role in preventing the amyloid deposition, 71 an epiphenomenon reported in lysosomal storage diseases 72 . Moreover, down‐regulation of GSN, involved in actin filament, may be directly connected with the disrupted interactions between actin and myosin in PD muscles.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, enrichment analysis of GO cellular components, showed that GPLD1 was attributed to lysosomal membrane, with a possible function in adapter protein recruitment and exocytosis. 70 TTR and GSN, down regulated in PD, are known for their role in preventing the amyloid deposition, 71 an epiphenomenon reported in lysosomal storage diseases. 72 Moreover, down-regulation of GSN, involved in actin filament, may be directly connected with the disrupted interactions between actin and myosin in PD muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA from peripheral blood leukocytes was isolated according to standard procedures as previously described (Jiao et al, 2014;Zhang et al, 2020). The DNA quality and quantity were assessed by both NanoDrop spectrophotometer 2000 (Thermo Scientific, Wilmington, DE, USA) and Qubit Fluorometer 3 (Life Technologies, Carlsbad, CA, USA).…”
Section: Genetic Testingmentioning
confidence: 99%